2007
DOI: 10.1063/1.2821113
|View full text |Cite
|
Sign up to set email alerts
|

Silicon nanowire solar cells

Abstract: Silicon nanowire-based solar cells on metal foil are described. The key benefits of such devices are discussed, followed by optical reflectance, current-voltage, and external quantum efficiency data for a cell design employing a thin amorphous silicon layer deposited on the nanowire array to form the p-n junction. A promising current density of ∼1.6mA∕cm2 for 1.8cm2 cells was obtained, and a broad external quantum efficiency was measured with a maximum value of ∼12% at 690nm. The optical reflectance of the sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
676
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 949 publications
(692 citation statements)
references
References 19 publications
9
676
1
5
Order By: Relevance
“…As a consequence, electron coupling to 'breathing modes' emerges that can not be described by conventional treatments of e-ph coupling. The consequences for physical properties such as scattering lengths and mobilities is significant: the mobilities for [110] grown wires is 6 times larger than for [100] wires, an effect that can not be predicted without the form we find for Si nanowire deformation potentials.Silicon nanowires, beyond having been successfully demonstrated as conventional semiconductor devices, 1-4 are beginning to be seen as the important blocks for novel energy harvesting applications, such as solar cells 5,6 and efficient thermoelectric devices. 7,8 All these applications rely on a high electronic conductivity of electrons, while in the latter a low phonon conductivity is also essential.…”
mentioning
confidence: 99%
“…As a consequence, electron coupling to 'breathing modes' emerges that can not be described by conventional treatments of e-ph coupling. The consequences for physical properties such as scattering lengths and mobilities is significant: the mobilities for [110] grown wires is 6 times larger than for [100] wires, an effect that can not be predicted without the form we find for Si nanowire deformation potentials.Silicon nanowires, beyond having been successfully demonstrated as conventional semiconductor devices, 1-4 are beginning to be seen as the important blocks for novel energy harvesting applications, such as solar cells 5,6 and efficient thermoelectric devices. 7,8 All these applications rely on a high electronic conductivity of electrons, while in the latter a low phonon conductivity is also essential.…”
mentioning
confidence: 99%
“…The benefits of the approach are considered to be a) increased light trapping from low volumes of material compared to thin films [10] and b) the separation of the processes of optical absorption and of carrier collection i.e. with absorption taking place as light travels down the length of a NW and carrier collection taking place over its width [11,12], this being postulated to minimise recombination loss provided the NW radius is smaller than the average carrier diffusion length. For the case of CdTe NW PV, modelling has indicated that 20% efficiency should be achievable [13], whereas 6% has been reached in practice, this being demonstrated using CdS nanopillars coated with CdTe [14].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It has been shown that they can successfully be integrated into devices such as sensors, NW transistors and solar cells of which some are already beyond the prototype stage. [3][4][5][6][7][8][9] Once a silicon p-n diode is reduced to a single NW, its opto-electronic characteristics can signicantly change due to an enhanced contribution of the electrical surface response, a strong current connement within the structure and resonant interaction with light. [10][11][12][13] These phenomena require in-depth understanding in order to successfully replace parts of today's technologies by advantageous NW building blocks.…”
Section: Introductionmentioning
confidence: 99%